Influences of end-point heating temperature on the quality attributes of chicken meat. Issue 6 (1st November 2016) - Chumngoen, W.; Chen, C.F.; Chen, H.Y.; Tan, F.J.
ABSTRACT: This study aimed to evaluate the changes in physicochemical, textural and sensory characteristics of broiler (BR) and Taiwan native chicken (TNC) pectoralis muscle heated at temperatures of 50–95°C. With increasing temperature, cooking loss, collagen solubility, shear force value and hardness, of samples increased in both chicken breeds. Rapid decreases in protein solubility were observed when the meat was heated to 50°C and gradually decreased thereafter. Meat from BRs and native chickens performed differently upon heating in certain characteristics. TNC meat had longer cooking time and lower myofibrillar fragmentation index than BR meat did. TNC meat had higher collagen content, shear force values and springiness but lower collagen solubility than BR meat did. BR meat had significantly higher onset and end transition temperatures than TNC meat did. In BR meat, a sensory analysis revealed that moisture release decreased and chicken flavour increased with increasing temperature. Protein solubility, cooking loss and the texture of heated meat were highly correlated. This study scientifically assessed the performances of the two breeds of chickens with different thermal treatments; producers could utilise the information to produce poultry products with more desirable qualities.